A multicentre retrospective clinico-histopathological review of 250 patients after parotidectomy. Issue 2 (February 2020) - Croonenborghs, T.M.; Van Hevele, J.; Scheerlinck, J.; Nout, E.; Schoenaers, J.; Politis, C.
Abstract: A clinicopathological review of parotid tumours treated surgically in two oral and maxillofacial surgery departments was conducted. The performance of fine needle aspiration cytology (FNAC) was also assessed. This retrospective study included 250 consecutive patients treated surgically for parotid gland-related tumours. Benign tumours ( n = 211, 84.4%) were more prevalent than malignancies ( n = 39, 15.6%). A predominance of pleomorphic adenoma (48.8%) was identified, and epithelial-myoepithelial carcinoma (3.6%) was the most common malignant tumour. Overall, the sensitivity and specificity of FNAC were 64% and 99%, respectively. Subgrouping resulted in sensitivity and specificity of 50% and 100% for clinically assisted FNAC versus, 72% and 99% for ultrasound guidance. Surgically, 31.6% underwent complete superficial parotidectomy and 28.4% underwent extracapsular dissection. Overall, facial nerve palsy was the most prevalent postoperative complication, affecting 29.2% (70/240); loss of function was transient in 21.2% (51/240) and permanent in 7.9% (19/240). Extracapsular dissection and superficial parotidectomy with facial nerve preservation were the treatments of choice when a benign tumour was suspected. Facial nerve palsy was quite frequent; treatment options however are scarce. Preoperative diagnostic workup using imaging and ultrasound-guided FNAC was essential in identifying malignancy so that surgical planning could be adapted.